2009
DOI: 10.1103/physrevc.80.065807
|View full text |Cite
|
Sign up to set email alerts
|

Sequential deconfinement of quark flavors in neutron stars

Abstract: A scenario is suggested in which the three light quark flavors are sequentially deconfined under increasing pressure in cold asymmetric nuclear matter as found, for example, in neutron stars. The basis for this analysis is a chiral quark matter model of Nambu-Jona-Lasinio (NJL) type with diquark pairing in the spin-1 single-flavor, spin-0 two-flavor, and three-flavor channels. Nucleon dissociation sets in at about the saturation density, n 0 , when the down-quark Fermi sea is populated (d-quark drip line) beca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…This can lead to interesting scenarios(cf. Blaschke et al 2009). However, in this work we model an EoS where light flavors appear at the same critical baryon chemical potential analogous to the results obtained with the "standard" approach for first-order phase transitions.…”
Section: Deconfinementmentioning
confidence: 99%
“…This can lead to interesting scenarios(cf. Blaschke et al 2009). However, in this work we model an EoS where light flavors appear at the same critical baryon chemical potential analogous to the results obtained with the "standard" approach for first-order phase transitions.…”
Section: Deconfinementmentioning
confidence: 99%
“…We observe an onset of strange quarks at much lower densities than the deconfinement phase transition. This leads to the simultaneous appearance of all flavours, in contrast to the commonly employed NJL-type models with sequential deconfinement [5,26]. We have found that the inclusion of the strange quark flavor lowers the onset of the deconfinement transition, but SFM parameters can be selected such that hybrid star sequences in the mass-radius diagram of two-and three-flavor quark matter are nearly indistinguishable.…”
Section: Discussionmentioning
confidence: 94%
“…The description of normal quark matter phases with two and three flavours is straightforward and shows the qualitative difference to bag models of quark matter already: light and strange quark flavours appear sequentially [29] due to the fact that different chemical potentials are required to reach the dynamically generated light and strange quark masses, so that strange quarks appear in cold quark matter only at high densities, eventually too high for CS interiors [30,31,32].…”
Section: Advanced Njl Model For High-density Quark Mattermentioning
confidence: 99%